Analisis Nilai Tambah Pemanfaatan Tunas Air Tembakau dalam Usaha Tembakau Rajang : Studi Kasus Bintang Muda Desa Kilensari Kecamatan Panarukan Situbondo - Mayangsari, Andina; Mikala, Kawakibi Ahmad Fadhil (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Tobacco shreds are one way of processing tobacco plants. Tobacco farming in Panarukan District is owned by the community. Kilensari Village is one of the tobacco producing areas in Panarukan District. Although the price of tobacco changes every planting season, high market demand encourages farmers to develop the tobacco industry. The high interest of farmers in cultivating tobacco in Kilensari Village has certainly given rise to businesses engaged in this sector, one of which is the processing of tobacco water shoots into Rajang tobacco. This business was founded by Mr. Kafi since the last 20 years with a slashing system to obtain raw materials from surrounding farmers. The purpose of this study was to determine the added value obtained from processing water shoots into sliced tobacco. This study was designed with a qualitative design and used a case study technique. Data were analyzed using the Hayami value-added method and described with quantitative and qualitative data. The results showed that sliced tobacco received an average added value of IDR 2,965 per kilogram, with a ratio of added value to average output value of 83.36 percent during the production process. This value added ratio is included in the high value added category because it is above 40%. This shows that the added value generated from the shredded water leaf tobacco farming business into water leaf shoots is very high. The shredded tobacco business produces 96% profit, with labor income of 3.53%.